Sustainability of Farmer Producer Organisations - The case of producer organisations involved in the production and marketing of ‘neera’ in the coconut sector - Thamban, C.; Jayasekhar, S.; Chandran, K.P.; Rajesh, M.K. (Journal of Plantation Crops, 2020)
Neera-the coconut inflorescence sap has been promoted as a potential value-added non-alcoholic beverage with abundant health benefits. The concerted effort of the stakeholder agencies could liberate the product from the policy regulations on its production under the excise act (known as ‘Abkari act’ in Kerala). Subsequently, the coconut producer federations (CPFs) in the State were granted licenses for ‘neera’ production and marketing. However, the majority of the CPFs discontinued the ‘neera’ enterprise, which they have initiated with greater enthusiasm. The present study is a modest attempt to trace the reasons for setbacks experienced in the ‘neera’ sector and also to provide a refined framework for revamping the sector. The details of licenses granted to the CPFs were sourced from the Department of Excise, Government of Kerala. The sample size of the study was 95 (13 CPFs who are still active and 82 CPFs who have discontinued). It was observed that the ‘neera’ value chain is in the evolving stage, and the withdrawal of the institutional support had detrimentally affected the confidence of the CPFs ventured into it. The availability of ‘neera’ technicians (tappers) and the high wage rates have evoked concerns on the profitability as well as the assurance of continuous supply of the product. The study categorically highlights the need for a restructured value chain of ‘neera’ with specific roles assigned to the stakeholders through the creation of functional linkages.